2010
DOI: 10.1093/jhered/esq077
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics of Physiological Plasticity and Local Adaptation in Killifish

Abstract: Evolutionary solutions to the physiological challenges of life in highly variable habitats can span the continuum from evolution of a cosmopolitan plastic phenotype to the evolution of locally adapted phenotypes. Killifish (Fundulus sp.) have evolved both highly plastic and locally adapted phenotypes within different selective contexts, providing a comparative system in which to explore the genomic underpinnings of physiological plasticity and adaptive variation. Importantly, extensive variation exists among p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 73 publications
4
65
0
1
Order By: Relevance
“…Previous studies have indicated that regulation of histone gene expression is associated with osmotic acclimation in killifish (Whitehead et al, 2011b;Whitehead et al, 2011a), and we detected several histone transcripts with transient upregulation in response to hypo-osmotic challenge (Fig.4E,F), two of which show salinitydependent upregulation (Fig.4E). Hypo-osmotic conditions can cause swelling of the nucleus and alter the structure and arrangement of chromatin, thereby potentially disrupting genome function (Finan and Guilak, 2010).…”
Section: Nucleosome Regulationsupporting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have indicated that regulation of histone gene expression is associated with osmotic acclimation in killifish (Whitehead et al, 2011b;Whitehead et al, 2011a), and we detected several histone transcripts with transient upregulation in response to hypo-osmotic challenge (Fig.4E,F), two of which show salinitydependent upregulation (Fig.4E). Hypo-osmotic conditions can cause swelling of the nucleus and alter the structure and arrangement of chromatin, thereby potentially disrupting genome function (Finan and Guilak, 2010).…”
Section: Nucleosome Regulationsupporting
confidence: 57%
“…At each sampling time point, plasma was collected by caudal puncture and was immediately isolated for ion measurements, one gill basket was excised and preserved for electron microscopy, and the other gill basket was preserved in RNAlater (Ambion, Austin, TX, USA) for transcriptomics. This experimental procedure is directly comparable to that of previous studies (Whitehead et al, 2011a;Whitehead et al, 2011b). All fish were treated in accordance with approved institutional animal care and use protocols.…”
Section: Materials and Methods Osmotic Challenge Experimentsmentioning
confidence: 88%
See 1 more Smart Citation
“…Gene expression was measured in gill tissues (the primary osmoregulatory tissue in fish; ref. 13) by using custom microarrays (14). Gene expression variation was characterized throughout the acclimation time-course and among populations, and patterns of population divergence were assigned to alternate evolutionary models: a putatively neutral model where population divergence in gene expression matches our isolationby-distance expectation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of larval physiological condition, in this case, total protein, Symbiodinium density, and size, complement these transcriptomic data. Our exploration of responses to a changing environment at the level of the transcriptome yields valuable information about current physiological thresholds, mechanisms driving changes in biological processes, and the potential for physiological plasticity and tolerance (e.g., Hofmann et al, 2008;Todgham and Hofmann, 2009;Whitehead et al, 2010).…”
Section: Introductionmentioning
confidence: 99%